2017
DOI: 10.3389/fmicb.2017.01911
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification and Biodiversity of Denitrifiers in a High-Mountain Mediterranean Lake

Abstract: Wet deposition of reactive nitrogen (Nr) species is considered a main factor contributing to N inputs, of which nitrate (NO3−) is usually the major component in high-mountain lakes. The microbial group of denitrifiers are largely responsible for reduction of nitrate to molecular dinitrogen (N2) in terrestrial and aquatic ecosystems, but the role of denitrification in removal of contaminant nitrates in high-mountain lakes is not well understood. We have used the oligotrophic, high-altitude La Caldera lake in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…The overall high proportion of denitrifying nitrite versus nitrous oxide reductase genes (∼30 nir : nosZ ratio on average) suggests a dominance of partial denitrification, especially in productive habitats dominated by nirS denitrifier communities (i.e., nirS -cluster showed nir : nosZ higher ratios compared to the other clusters, WMW test, p < 0.01). This observation agrees with Castellano-Hinojosa et al (2017) who found high N 2 O/N 2 emissions in a productive, shallow warm Mediterranean mountain lake, as well as Myrstener et al (2016) who demonstrated that addition of nitrate, phosphorus and labile C to sediments from a boreal lake resulted in higher relative N 2 O production compared to addition of nitrate alone. Other studies have shown that higher nir : nosZ1 ratios in the sediments of boreal lakes were associated with hypolimnion N 2 O excess, as well as increased phosphate and nitrate concentrations (Saarenheimo et al, 2015a).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall high proportion of denitrifying nitrite versus nitrous oxide reductase genes (∼30 nir : nosZ ratio on average) suggests a dominance of partial denitrification, especially in productive habitats dominated by nirS denitrifier communities (i.e., nirS -cluster showed nir : nosZ higher ratios compared to the other clusters, WMW test, p < 0.01). This observation agrees with Castellano-Hinojosa et al (2017) who found high N 2 O/N 2 emissions in a productive, shallow warm Mediterranean mountain lake, as well as Myrstener et al (2016) who demonstrated that addition of nitrate, phosphorus and labile C to sediments from a boreal lake resulted in higher relative N 2 O production compared to addition of nitrate alone. Other studies have shown that higher nir : nosZ1 ratios in the sediments of boreal lakes were associated with hypolimnion N 2 O excess, as well as increased phosphate and nitrate concentrations (Saarenheimo et al, 2015a).…”
Section: Discussionsupporting
confidence: 91%
“…Links between taxonomic composition and functional potential has been observed in previous works in lakes based on metagenomes or sequencing of functional genes. The occurrence of several proteobacterial families, in particular, Rhodobacteraceae (Alphaproteobacteria), Methylococcaceae (Gammaproteobacteria), and Burkholderiales, Comamonadaceae and Rhodocyclaceae (Betaproteobacteria) has been shown to be strongly associated with denitrification gene presence or abundance (Vila-Costa et al, 2014; Peura et al, 2015; Saarenheimo et al, 2015b; Castellano-Hinojosa et al, 2017; Chen R. et al, 2017). These taxa were also highly abundant in samples within the nirS -denitrifier and mixed functional gene communities, which included nirK -type denitrifiers.…”
Section: Discussionmentioning
confidence: 99%
“…However, they were not able to evaluate whether an enhancement of denitrification could be an alternative explanation due to the lack of empirical information. The difficulty of the measuring DEN rates at low N r concentrations may justify why remote systems have been overlooked with a few exceptions (Castellano‐Hinojosa et al, ; McCrackin & Elser, ; Vila‐Costa et al, ). Indeed, it has been only one attempt to estimate DEN E a in these systems (Myrstener et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Those processes of reactive nitrogen removal are performed mainly by anaerobic bacteria inhabiting environments with low O 2 concentration, such as subsurface soils and sediments and anaerobic hypolimnion of lakes. Unexpectedly, active and diverse communities of denitrifying bacteria have been found in some well-oxygenated ecosystems, such as high-mountain lakes, where denitrification can explain the seasonal decline in nitrate concentration observed in the water column [ 32 ]. On the whole, aquatic denitrification may be on the rise coincident with increasing ocean deoxygenation, a trend that may greatly reduce productivity in nitrogen-limited waters by disadvantaging nitrogen-needy non-nitrogen fixing phytoplankton and heterotrophic bacteria—with impacts extending all the way up in the food chain [ 33 ].…”
Section: Sunny Side Up: Fusion-style Cooking With Supplements and mentioning
confidence: 99%